2020
DOI: 10.1177/0363546520935855
|View full text |Cite
|
Sign up to set email alerts
|

Human Rotator Cuff Tears Have an Endogenous, Inducible Stem Cell Source Capable of Improving Muscle Quality and Function After Rotator Cuff Repair

Abstract: Background: The muscle quality of the rotator cuff (RC), measured by atrophy and fatty infiltration (FI), is a key determinant of outcomes in RC injury and repair. The ability to regenerate muscle after repair has been shown to be limited. Purpose: To determine if there is a source of resident endogenous stem cells, fibroadipogenic progenitor cells (FAPs), within RC injury patients, and if these cells are capable of adipogenic, fibrogenic, and pro-myogenic differentiation. Study Design: Controlled laboratory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 53 publications
3
52
0
Order By: Relevance
“…111 Feeley et al demonstrated that RC FI, fibrosis, and FAP number increased with tear size and thickness in human subjects. 100 Furthermore, the FAPs from full thickness tears displayed greater fibrogenic and adipogenic differentiation capacity in vitro than those harvested from partial tears, suggestive of FAP epigenetic changes across tear states. These studies represent important steps in confirming the cellular actors involved in human RC FI and fibrosis.…”
Section: Fap Contribution To Rc Fi and Fibrosismentioning
confidence: 94%
See 3 more Smart Citations
“…111 Feeley et al demonstrated that RC FI, fibrosis, and FAP number increased with tear size and thickness in human subjects. 100 Furthermore, the FAPs from full thickness tears displayed greater fibrogenic and adipogenic differentiation capacity in vitro than those harvested from partial tears, suggestive of FAP epigenetic changes across tear states. These studies represent important steps in confirming the cellular actors involved in human RC FI and fibrosis.…”
Section: Fap Contribution To Rc Fi and Fibrosismentioning
confidence: 94%
“…44 Recently, FAPs from the human RC have been shown to adopt a beige fat phenotype in vitro after treatment with the beta-3 agonist amibegron. 100 Furthermore, these beige-like FAPs displayed markedly increased gene expression of IGF-1 and follistatin. Beta-3 agonists, such as amibegron (SR58611A), have been shown to enhance brown fat characteristics, which may point to a potential clinical use in RC injury.…”
Section: Potential Therapeutic Role Of Faps In Rc Regenerationmentioning
confidence: 98%
See 2 more Smart Citations
“…HE and Masson staining were conducted based on the established method. 34,35 The thickness of joint capsule was obtained by five random measurements to obtain a mean value using ImageJ software. The relative thickness of joint capsule in different groups compared to group NC was calculated.…”
Section: Shoulder Sample Harvest and Analysismentioning
confidence: 99%